The key antecedent and consequences of destination image in a mega sporting event - Yunduk Jeong; Suk-Kyu Kim (South African Journal of Business Management, 2019)
Background: One of the major challenges for marketing managers in the tourism industry faces is to improve destination image because of its huge impact on satisfaction and recommendation intentions. In this study, we identified event quality of mega sport events as a key antecedent that influences destination image.Objective: This study was undertaken to investigate the structural relationships between event quality, destination image, tourist satisfaction and recommendation intention with emphasis on the mediating effect of tourist satisfaction on relations between destination image and recommendation intention in the context of mega-scale sporting events.Method: Responses obtained from 342 international tourists visiting Pyeongchang, South Korea were collected and analysed. The validity and reliability of the involved measures were examined through conducting confirmatory factors, Cronbach's alpha, and correlation analyses. A structural equation modelling analysis was conducted to investigate the relationships between the research variables.Results: The results were: (1) Event quality is a critical factor in influencing destination image, (2) destination image acts as an antecedent of tourist satisfaction and recommendation intention, (3) tourist satisfaction leads to recommendation intention and (4) tourist satisfaction partially mediates the relationship between destination image and recommendation intention. The practical implications were: (1) Destination marketers should utilise the Olympic legacy, (2) destination marketers should actively use social media to improve the destination image, and (3) local authorities should improve accessibility of destination through the construction of transportation infrastructure.Conclusion: It is meaningful to: (1) include event quality in tourism destination image-satisfaction-behavioural intentions models, (2) mega sporting events should be considered important aspects of marketing strategies aimed at improving destination image and its relevant variables and (3) we reveal empirical evidence that tourist satisfaction partially mediates the relation between destination image and recommendation intention. Accordingly, this article provides a step towards a richer and more inclusive understanding of destination marketing strategies.
Keywords: 650